Synthesis and Characterization of Mesoporous Silica Templates (KIT-6, SBA-15) and Mesoporous Platinum. (1st August 2022) - Parkash, Anand; Solangi, Nizamuddin; Wahocho, Shafeeque Ahmed; Channa, Abdul Sami; Inam, Muhammad Ali; Ali, Shafqat
Abstract : Using unsupported catalysts also improved stability during electrochemical reactions and high durability due to their non-corrosive component, carbon. Advanced mesoporous architectures were created in which the pore and metal composition are controlled at the nanoscale level. Rigid template-assisted synthesis, which makes periodic porosity in the solid, is used to create mesoporous platinum (Pt) and Pt bimetallic catalyst. The ability to control the composition, shape, and porous architecture of Pt and Pt bimetallic combinations, eliminating the carbon corrosion problem, improved the activity of the catalyst. Hence, 3D bicontinuous mesoporous silica KIT-6 and 2D mesoporous silica SBA-15 were synthesized. Ordered mesoporous silica prepared has uniform mesopores (7.9 and 7.3 nm for KIT-6 and SBA-15, respectively) and high specific surface areas 772 m 2 .g −1 (for KIT-6) and 943 m 2 .g −1 (for SBA-15). These rigid silica templates were employed to produce mesoporous metal particles for fuel cell electrocatalyst.